2021
DOI: 10.3390/su13126688
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Soil Hydraulic Parameters and Evaluation of Water Dynamics and Nitrate Leaching in the Unsaturated Layered Zone: A Modeling Case Study in Central Croatia

Abstract: Nitrate leaching through soil layers to groundwater may cause significant degradation of natural resources. The aims of this study were: (i) to estimate soil hydraulic properties (SHPs) of the similar soil type with same management on various locations; (ii) to determine annual water dynamics; and (iii) to estimate the impact of subsoil horizon properties on nitrate leaching. The final goal was to compare the influence of different SHPs and layering on water dynamics and nitrate leaching. The study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Other studies showed similar results, in which nitrogen was the main predictor of nitrates (Oehler and Elliott 2011). Nitrogen leaches when transformed into nitrate form, and the main issue then with nitrates is their mobility in the soil and the fact that they can persist in SW and GW (Defterdarović et al 2021). Agricultural activity is the main source of nitrogen in the watershed (Dorado-Guerra et al 2021); therefore, DP is the most probable cause for the higher nitrate probabilities and the increase of the nitrate concentrations in the river.…”
Section: Use Of Extrinsic Features Of Surface Water Bodies and Their ...mentioning
confidence: 55%
See 1 more Smart Citation
“…Other studies showed similar results, in which nitrogen was the main predictor of nitrates (Oehler and Elliott 2011). Nitrogen leaches when transformed into nitrate form, and the main issue then with nitrates is their mobility in the soil and the fact that they can persist in SW and GW (Defterdarović et al 2021). Agricultural activity is the main source of nitrogen in the watershed (Dorado-Guerra et al 2021); therefore, DP is the most probable cause for the higher nitrate probabilities and the increase of the nitrate concentrations in the river.…”
Section: Use Of Extrinsic Features Of Surface Water Bodies and Their ...mentioning
confidence: 55%
“…Its main source in Europe is diffuse pollution (Grinsven et al 2015, Alcon et al 2022, whereby nitrogen leaches when transformed into nitrate form. The main issue, then, with nitrates is their mobility in soil, and the fact that they can persist in surface water (SW) and groundwater (GW) (Defterdarović et al 2021), contributing to poor water quality and eutrophication (Pang et al 2022). Currently, the ecological status of more than half the water bodies in the EU is assessed as poor (Poikane et al 2019), contrary to the requirements of the Water Framework Directive (WFD) and Nitrates Directive (Directive 91/676/EEC).…”
Section: Introductionmentioning
confidence: 99%
“…A more pronounced water movement was observed at the footslope owing to the slight differences in the bulk density and total porosity, which can lead to differences in the water flow, i.e. macropores will cause increased water movement [35], or it could even be a result of preferential flows [8,11,48]. Furthermore, the surface runoff was more pronounced at the hilltop, resulting in a higher water volume at footslope positions.…”
Section: Determination Of the Water Flow Using Lysimeters And Sensorsmentioning
confidence: 99%
“…The topsoil had a better soil structure in general with a higher C org content, lower bulk density, and higher porosity, resulting in more aerated conditions [35]. However, according to Figure 5, at the hilltop, the soil texture changes to a heavier silty clay loam and silty clay in the deeper layers (50-100 cm).…”
Section: Physical Chemical and Hydraulic Characteristicsmentioning
confidence: 99%
“…The HYDRUS (2D/3D) model [35] has been widely used in the analysis of water, heat and solute transport in variably saturated porous media in agricultural systems [36][37][38][39][40]. In this study, we developed a simple NLSB treatment for a post-construction earth embankment using casing-wells to backfill NaCl-laden soil, which acts as a barrier against subterranean termites.…”
Section: Introductionmentioning
confidence: 99%